Formal and informal institutions in the selection of candidates in the colombian sub-national. elections 2011 (2014)
The candidate selection process by some Colombian political parties at the subnational level are given in the interaction between formal institutions (Constitution, laws, statutes and rulings) and informal (electoral pacts, parliamentary pen and strategies for expanding the partisan presence ). Although routinization processes tend to be affected by the existence of informal institutions, which in turn contribute to the parties resolve their internal disputes. All in all political parties tend to be pragmatic in making decisions about which candidate to endorse, and therefore resort to either formalized rules or do not play.